Multiomics characterization of breast angiosarcoma from an Asian cohort reveals enrichment for angiogenesis signaling pathway and tumor-infiltrating macrophages - Ko, Tun Kiat; Guo, Zexi; Kannan, Bavani; Lim, Boon Yee; Lee, Jing Yi; Li, Zhimei; Lee, Elizabeth Chun Yong; Teh, Bin Tean; Chan, Jason Yongsheng (Frontiers in Immunology, 2025)
IntroductionRecent epidemiological data suggests a rising incidence of breast angiosarcoma (AS-B) in the Western population, with over two-thirds related to irradiation or chronic lymphedema. However, unlike head and neck angiosarcoma (AS-HN), AS-B disease characteristics in Asia remain unclear.MethodsWe examined clinical patterns of angiosarcoma patients (n = 176) seen in an Asiantertiary cancer center from 1999 to 2021, and specifically investigated the molecular and immune features of AS-B in comparison to AS-HN. Data from whole genome sequencing (WGS), NanoString gene expression profiling and 10x Genomics Visium spatial transcriptomics were analyzed.ResultsMajority of cases were AS-HN (n = 104; 59.1%), while AS-B (n = 16, all females) accounted for 9.1% of the cases. The median age at diagnosis was 43 years (range, 26 to 74). Based on WGS, 4 of the 7 AS-B had non-synonymous somatic variants in 47 genes (range, 2 to 28 per case). These genes were functionally annotated and were enriched in cancer-related pathways such as regulation of cell differentiation, VEGFR and receptor tyrosine kinases signaling pathways. By NanoString gene expression profiling, ASB, compared to AS-HN, were enriched for angiogenesis, notch signaling and metastasis-associated matrix remodeling pathways. Additionally, AS-B were enriched for macrophages and CD8+ T cells expression signatures. Similarly, Visium spatial transcriptomics showed that AS-B were enriched for macrophages and T-cells.DiscussionIn conclusion, in our AS-B cases, we observed a convergence of both mutational and expression signatures on angiogenic-related pathways. Thus, anti-angiogenic therapy could be an option to treat AS-B.